A South African perspective on some critical issues regarding the OECD model tax convention on income and on capital, with special emphasis on its application to trusts - Du Plessis, Izelle (Stellenbosch University, 2014)
Trusts are used for a variety of purposes, both in South Africa and abroad. Like so many other entities, trusts often do not function only in one jurisdiction and may therefore be exposed to international double taxation. South Africa, like most other states, enters into bi-lateral double taxation treaties, to limit the effects of international double taxation. Most of these treaties are based on the OECD Model Tax Convention on Income and on Capital (the OECD MTC). The South African trust is a unique creature. It is not based on the dual ownership concept on which most common law trusts are based, yet, it is not a juristic person either. The question that this research aims to address is how South Africa will interpret and apply certain provisions of the OECD MTC to trusts. Although the South African position is investigated, it is compared to the positions of the United Kingdom, Canada and the Netherlands. The dissertation starts with an analysis of the trust law in each of the relevant states, followed by an overview of the taxation regime governing trusts (and the parties thereto) in each state. The status of double taxation treaties and their interpretation are examined before certain critical provisions of the OECD MTC are analysed to determine how South Africa will apply these provisions to trusts. Hence it is explored whether a trust will be regarded as a person, whether it may be a resident and a beneficial owner for purposes of the OECD MTC. Furthermore, possible solutions for conflicts of attribution in the application of double tax conventions to trusts are investigated. The dissertation concludes that South Africa will regard a trust as a person for purposes of the OECD MTC. Moreover, some types of trusts may be viewed as residents and as beneficial owners for purposes of the OECD MTC. The solution proposed in the OECD’s Partnership Report should be applied to resolve conflicts of attribution involving trusts.
URI: http://hdl.handle.net/10019.1/95878
Keywords: Double taxation; Income tax; International taxation; OECD Model Tax Convention; South Africa; Taxation; Treaties; Trusts and trustees

Cross-border resolution of banking groups: old demons, current progress, future challenges - Pnevmonidis, Ilias (Université de Genève, 2014)
This contribution focuses on the development of bank resolution regimes as a credible antidote to the ‘too big to fail' problem. The main objective of the analysis is to demonstrate the repercussions and challenges resulting from the implementation of bank resolution schemes on a cross-border level. This work is a selective survey of specific legal questions, which remain relatively unaddressed by academic literature and international standard-setting bodies (e.g. bank resolution triggers or safeguards for bank creditors under bank resolution) or still problematic (e.g. resolution planning or cooperation and information exchange between resolution authorities), in particular when applied in a cross-border context. The author aims to shed more light to the complexities of cross-border bank resolution while trying to answer to the fundamental question: have we ended the ‘too big to fail' problem?
Keywords: Bank-failures; Bank-insolvency; Bank-resolution; Financial-crisis; Insolvency; Systemic-risk; Too-big-to-fail

Bringing Formal Business Laws to Cameroon’s Informal Sector: Lessons and Cautions from the Tax Law Example - Dickerson, Claire Moore (Washington University Global Studies Law Review, 2014)
A substantial majority of non-agricultural workers in a developing country such as Cameroon engage in legal businesses below the governmental radar, that is, in the informal sector. Because that segment of the Sub-Saharan economy is critical to subsistence within the region, and because the financial crisis has expanded the informal sector in the Global North, developing economies’ experience with the informal sector is of world-wide relevance. Formal business laws do exist in the formal sector; however, trying to move informal-sector workers to the formal sector where these laws already offer some protection can disrupt the entrepreneurs’ ability to sustain themselves, and to contribute to the national economy. A pilot study in five Cameroonian markets is thus of general interest when it reveals that entrepreneurs there do not benefit from formal business laws, which in turn limits their ability to borrow and their willingness to lend. The same study also suggests that tax literature has interesting, non-coercive strategies to improve tax compliance in ways that may be applicable to facilitating the introduction of formal business laws to the informal sector, instead of forcing informal-sector workers into the formal sector. The tax-morale literature recommends deploying strategies of reciprocity, in addition to providing public goods and services—strategies that encourage compliance—instead of using governmental power to extract tax payments. Similarly, tax-based strategies can apply to business laws while informal-sector workers remain in the informal sector, even though the government’s posture vis-à-vis commercial actors is less direct than vis-à-vis taxpayers. The experience of Cameroon’s informal sector with formal tax law thus provides important insights on steps within the government’s control that would not only improve tax compliance, but would also bring formal business laws and their transaction-cost-reducing potential to the informal sector. The pro-business strategy is to apply tax-morale learning, which calls for government authorities to enter into a reciprocal relationship— respectful and communicative—with private parties and to focus on investing in basic infrastructure.

An evaluation of the predictive value of bank fair values - Ehalaiye, Oludimu Oluseun (Victoria University of Wellington, 2014)
This thesis examines whether the net asset fair values of banks possess predictive ability for the banks’ future cash flows and earnings. This is an important issue considering the arguments for and against the wider use of fair value accounting for banks’ financial instruments and the claim by some that fair values during economic recessions (where markets may be illiquid) are irrelevant and largely unreliable. A number of studies have found that the explanatory power of bank fair values when compared to traditional historical cost are more value-relevant based on capital market reactions. However, there is a very limited literature on how bank fair values are related to the future performance (e.g. earnings and cash flow) of banks. This study fills this gap by providing empirical evidence on the relationship between U.S. bank fair value disclosures and banks’ future performance as measured by operating cash flows and earnings over a three-period future horizon. Furthermore, the thesis provides evidence on the relationship between bank fair values, in terms of the levels classification introduced during the 2008 global financial crisis, and the future performance of banks, thus showing whether market illiquidity affected the underlying relationships. The study examines two distinct periods. The first study period, 1996-2005, was based on annual data of banks with minimum total assets of $US150 million as of year 1996. The second study period from 2008-2010 (this period encompassed the global financial crisis period and also the levels classification of bank fair values according to SFAS 157), was based on quarterly data of banks with minimum total assets of $US150 million as of the first quarter of 2008. The thesis provides strong evidence that there is a predictive relationship between bank fair values and future bank performance. The evidence is strong during the first study period from 1996 to 2005 where the current net asset fair values of on-balance sheet financial instruments of banks were significantly associated with future operating cash flows and operating earnings of such banks over a three-year future time horizon. However, the predictive relationship between net asset bank fair values and operating cash flows is stronger than the predictive relationship between net asset bank fair values and operating earnings. In the second study period, from 2008 until 2010 the empirical results show strong evidence that there is a predictive relationship between level 1 and level 2 bank fair values and future operating cash flows. The findings from the empirical results were that the current quarter’s level 1 and level 2 net asset fair values of banks were significantly associated with the future quarters’ operating cash flows of such banks. The level 3 net asset fair values of such banks in most cases were not significantly associated with the banks’ future quarterly operating cash flows. The corresponding relationships for operating earnings were that the current quarter’s level 1 net asset fair values of banks were positively associated with the future quarters’ operating earnings of such banks. However, the level 2 net asset fair values of banks were negatively associated with the future quarters’ earnings of such banks. This result is in contrast to the results obtained when the predictive relationship between level 2 bank fair values and future operating cash flows was evaluated, where it is found that both level 1 and level 2 net asset bank fair values are positively related to future quarterly bank cash flows. Further empirical analysis showed that a possible reason behind this disparity was that there was a structural change in the relationship between bank operating cash flows and operating earnings over the course of the first and second study periods, where, in particular, for the second study period (which includes the period of the global financial crisis) there was a systematic downward bias in operating earnings relative to the operating cash flows of the sampled banks. This in turn makes operating earnings a poor proxy for operating cash flows during the second study period. The findings from this study provide confirmation that net asset fair values have predictive ability as argued by Ball (2008); Barth (2006b) and Tweedie (2008). The study findings that net asset fair values have predictive ability is consistent with the FASB’s view that the asset values shown in firm financial statements should communicate information about the potential future financial performance of the affected firms (FASB 2010:17). Furthermore, the study also confirms that objectively determined bank fair values based on market prices rather than model based bank fair values provide greater predictive value in relation to future performance as measured by operating cash flows. Lastly, this thesis showed that during the first study period (where there was no financial crisis) that bank size, capital adequacy and growth prospects, had little impact on the results obtained, while for the second study period, there were cases where bank size and bank capital ratios did have a significant impact on the predictive relationship between bank fair values and future cash flows. The study contributes to the fair value accounting and accounting standard-setting literature and highlights that fair values have predictive ability, especially with respect to future operating cash flows of banks, both during and outside of periods of financial crisis.
Keywords: Economic forecasting; Fair value; Predictive value

A macro-financial theory of corporate financing and forecast modelling of market movements - Sutton, David (Victoria University of Wellington, 2014)
This thesis identifies a gap in existing theories of corporate finance. This gap is an implication of a Keynesian-Minskian analysis of markets and market-based economies. From a founding theoretical perspective rooted in the view that markets are not reliably efficient the case is developed that past price trend extrapolation is an important factor in corporate financing decisions. At a macro-financial level, companies repurchase equity over periods of strong market rises, while increasing debt at the same time. During periods of sustained, substantial market decline debt is retired and large new equity issues occur. This change in corporate financing is implicitly expensive as relatively low prices are realised for the new stock issued at these times. These factors suggest that conventional theories of corporate financing decisions that rely on corporate rationality and optimisation do not provide a compelling fit with observations in the period 1980-2012. Moreover, inference to Minsky’s (1986) argument that companies are compelled through market declines to shore up their balance sheets provides a better fit with the evidence. These arguments form the basis for the development of the ‘extrapolative expectations’ theory of corporate finance. The second major development in this thesis draws on the theoretical development outlined above to create market movement description and prediction models. These models operate on data drawn from the US Standard & Poors 500 index over the period 1980-2012. Two primary models are developed using binomial logistic regressions. The dichotomous dependent variables are drawn as quarters of market rise (1) or no rise (0), and market falls (1) or no fall (0), respectively for the ‘buy’ model and the ‘sell’ model. Variables tested and those found to add to an explanation of the dependent variables include: corporate debt flows, corporate equity flows, corporate dividend flows, interest rates, market volumes, and historical market levels. Each variable is tested for up to ten lags (two-and-a-half years). Collectively, the variables add to our understanding of those factors influencing (or at the least, signalling) market levels, enabling quarter ahead market forecasts to be made with greater accuracy than arises from an assumption of a random walk. This conclusion crystallises the view that company macro-financial flows and prices are an important cause or signal of future market direction.
Keywords: Corporate financing; Financial Accounting; International Accounting; Macro-financial; Minsky